Analysis of Leadership Style, Motivation, and Work Facilities on Employee Job Satisfaction at the Binjai City Environmental Agency - Husin, Beni; Rahayu, Sri; Sebayang, Saimara A.M (Journal of Management, Economic, and Accounting, 2026)
This study aims to analyze the influence of leadership style, employee motivation, and the condition of work facilities on employee job satisfaction. The research was conducted at the Environmental Agency of Binjai City using a quantitative research approach. The sampling technique applied was saturated sampling, in which all 53 employees of the agency were included as respondents. Data were analyzed using multiple linear regression.The findings indicate that leadership style, work motivation, and work facilities have a significant and positive effect on employee job satisfaction at the Environmental Agency of Binjai City. Specifically, better leadership practices are associated with higher levels of employee satisfaction. In addition, higher work motivation is positively correlated with increased job satisfaction. Likewise, the availability and quality of work facilities make a meaningful contribution to employee job satisfaction in this institution.